Pengembangan Media Pembelajaran Interaktif Berbasis Canva untuk Meningkatkan Hasil Belajar Siswa di MA Al-Bairuny - Rahmadyani, Devi Eka Putri; Ma’arif, Iin Baroroh (Lembaga Yasin AlSys, 2025)
The low learning interest of students at MA Al-Bairuny is primarily caused by monotonous teaching processes and the dominance of lecture-based methods that limit active student participation. In this context, information technology-based learning media is urgently needed to enhance engagement and motivation. This study aims to develop and assess the feasibility of Canva-based interactive learning media to improve student learning outcomes. The research employed a Research and Development (R&D) method using the ADDIE model, encompassing the stages of Analyze, Design, Development, Implementation, and Evaluation. The research subjects were 27 tenth-grade students. Data were collected through observation, interviews, documentation, and questionnaires. Validation results indicated a feasibility level of 88% from media experts and 82% from content experts. Student response questionnaires yielded a score of 92.5%, showing that the developed media was highly engaging. The study concludes that Canva-based interactive learning media is highly feasible and effective for fostering student enthusiasm and interest in learning. The findings imply that technology-based media can serve as a relevant alternative solution to low learning interest while supporting the creation of a more participatory and enjoyable learning process.